Kingdom of the Netherlands : Netherlands; Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Overall competitiveness of the Dutch economy seems adequate, but domestically produced exports have lost market share recently. Over the past three decades, globalization has greatly influenced economies as countries have become more integrated. Empirical studies on business cycles synchronization and transmission of shocks among countries have provided conflicting results. In its descriptive part, this study concludes that Dutch export competitiveness is not a problem so far. This also finds that the Netherlands is relatively more exposed to supply-driven shocks while Germany is more exposed to demand-driven shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet